Modelling of a Reversible SOC in Ansys Fluent. (10th July 2019) - Herrmann, Stephan; Ong, Zhan Zhoon; Hauck, Maximilian; Hauser, Michael; Fischer, Felix; Weinrich, Jeremias; Gaderer, Matthias; Spliethoff, Hartmut
Abstract : Reversible Solid Oxide Cells (SOC) are quite susceptible to variations in operating parameters, and especially the switching of operating modes is not yet well understood. Effects like thermal stress from changes in the current density pattern, as well as carbon deposition and nickel oxidation can destroy SOC. Thus, in order to design a robust SOC system a SOC stack model has been built in ANSYS Fluent 17.0. In this work, this model is used to study the impact of operating mode transition from fuel cell to electrolysis on the stack. It is found that the thermal gradients resulting from switching operation modes are largely depending on the gas compositions fed during both operating modes. Therefore, at fixed operating temperature especially by adjusting the gas feeds thermal gradients can be flattened, so that their effect on the lifetime of the SOC can be significantly reduced.